Ricardo Palma's social readings - Reyes Tarazona, Roberto (2019)
This text offers an overview of the reception, acceptance of the work of Ricardo Palma at various times in our history, from the publication of the first collection of the Peruvian Traditions (1872). There are some reactions of Peruvian critics and intellectuals about the work of the traditionist, although references are also made to those of other nationalities (Ibero-American), making references to the existing cultural and political environment. It concludes with the re-meaning of life and work of Palma, based on the actions of the Ricardo Palma Institute, in the new century, and its impact on the interest of the author of the traditions.